A case of recurrence of adult-onset Still's disease in the third trimester: a case report and literature review - Satoshi Hosoya; Miyuki Sadatsuki; Shinji Izuka; Hiroyuki Yamashita; Hajime Oishi (BMC, 2021)
Abstract Background Adult-onset Still's disease (AOSD) is a self-inflammatory disease showing macrophage and neutrophil activation by inflammatory cytokines such as TNF-α, IL-6, and IL-18. Although some cases with the flare of AOSD during pregnancy have been reported, most had flares in the first or second trimester and few had flares in the third trimester. In this report, we present the case of a patient with recurrent flare of AOSD in the third trimester and discuss the management of AOSD in the third trimester with the review of previous literatures. Case presentation A 38-year-old woman in complete AOSD remission without medication presented with impaired liver function, low platelet count, mild fever, abdominal pain, splenomegaly, and elevated ferritin and IL-18 levels at 30 gestational weeks. Although the laboratory data and physical examination finding suggested HELLP syndrome or acute fatty liver of pregnancy and we considered the termination of her pregnancy, her fetus was in a reactive status. Considering her fetal status, some specific findings of AOSD, and her AOSD history, we and rheumatologists diagnosed her with AOSD recurrence and started systemic steroid therapy. In her clinical course, three flares of AOSD occurred, twice in the third trimester and once in postpartum; twice systemic steroid pulse therapies were then needed. Ultimately, a healthy infant was delivered transvaginally at 36 gestational weeks spontaneously. Conclusions Specific findings of the flare of AOSD such as fever, splenomegaly, elevated ferritin and IL-18 levels, and fetal status could be useful findings for differentiation from HELLP syndrome and AFLP in the third trimester. With the careful management supported by rheumatologists, patients complicated with the flare of AOSD may continue their pregnancy longer than we expected.